Epinephrine Promotes IL-8 Production in Human Leukocytes via an Effect on Platelets - Engstad, Charlotte Sissener; Lund, Trine; Østerud, Bjarne (Thrombosis and Haemostasis, 1999)
Interleukin-8 (IL-8) is generally accepted to be an important mediator of a number of acute and chronic inflammatory diseases and is produced by monocytes upon stimulation by lipopolysaccharide (LPS). Epinephrine has been reported by several groups to suppress activation of monocytes in response to LPS, and the aim of the present study was to examine the effect of epinephrine on LPS induced IL-8 production using whole blood as a model system. Epinephrine increased LPS induced IL-8 production in a dose-dependent manner in the whole concentration range (0.001–100 μM) and 1 μM epinephrine increased IL-8 levels with 125%. Epinephrine per se had no effect on IL-8 levels. The potentiating effect of epinephrine was mediated by blood platelets, since IL-8 levels in samples containing platelets and stimulated with LPS and epinephrine (1–100 μM) were significantly higher (p <0.05) than in control samples containing no platelets. This effect of platelets seemed to be due to platelet release products, since addition of 25 μl platelet lysate supernatant to whole blood increased LPS induced IL-8 production with 100% and a similar effect was observed in freshly isolated mononuclear cells resuspended in plasma. Upon addition of 50 μg/ml of the carboxyterminal peptide of platelet factor 4 (PF4(58-70)) to whole blood, LPS stimulated IL-8 levels were increased with 115%, whereas in mononuclear cells, 20 μg/ml PF4(58-70) enhanced IL-8 production with 40%. We demonstrate for the first time that epinephrine promotes LPS induced production of IL-8 in whole blood via an effect on blood platelets. This potentiating effect of platelets is shown to be due to platelet granule contents, and platelet factor 4 (PF4) is suggested to be one of several platelet granule proteins promoting LPS induced IL-8 production in whole blood.